2004
DOI: 10.1038/sj.pcan.4500695
|View full text |Cite
|
Sign up to set email alerts
|

Impact of training level of urology residents on the detection of prostate cancer on TRUS biopsy

Abstract: The objective of this study is to evaluate the performance of urology residents at each training level in detecting prostate cancer with transrectal ultrasound-guided (TRUS) biopsy. The inclusion criteria were: (1) prostate-specific antigen (PSA) 4-10 ng/ml; and (2) 10-12 cores per biopsy session. Data from repeat biopsy sessions were excluded. Overall prostate cancer detection rate for 170 patients was 39.4%. PSA, digital rectal examination (DRE), and prostate volume were predictors of cancer detection. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The overall cancer detection rate in this study was previously reported at almost 50%, 14,15 which is higher than in traditional series with a rate of 27% to 44% in similar cohorts. [22][23][24][25][26][27][28] This is similar to findings in studies of saturation techniques for initial biopsy with a 43% to 46% rate. 19,29 We believe that our high detection rate is explained by solid techniques, significant case load, excellent equipment, end firing probes and ultrasound to find hypoechoic lesions which, as we already reported, increases the yield.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall cancer detection rate in this study was previously reported at almost 50%, 14,15 which is higher than in traditional series with a rate of 27% to 44% in similar cohorts. [22][23][24][25][26][27][28] This is similar to findings in studies of saturation techniques for initial biopsy with a 43% to 46% rate. 19,29 We believe that our high detection rate is explained by solid techniques, significant case load, excellent equipment, end firing probes and ultrasound to find hypoechoic lesions which, as we already reported, increases the yield.…”
Section: Discussionsupporting
confidence: 88%
“…22 However, emerging data suggest that equipment has a role, such that end fire probes have a higher cancer detection rate than side fire probes (45.8% vs 38.5%). 28 In our study cancer detection differences were likely based on technique rather than on patient or equipment factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings are consistent with two prior studies by Mariappan et al that described an association between surgeon experience and adequate muscle-containing bladder specimens [12,13]. Further, urological studies to date have demonstrated conflicting findings when assessing the impact of residents on surgical outcomes; however, when focusing on endoscopic studies, a disadvantageous influence appears to exist [3,4,[14][15][16][17][18]. A recent study of 8152 transurethral resection procedures showed that resident participation was associated with increased odds of prolonged operative time and 30 day hospital readmission rates [19].…”
Section: Discussionsupporting
confidence: 92%
“…Although urology trainees performed both FG and TRUS biopsies, with equal experience in both approaches, the learning curve associated with TRUS biopsy might impact the quality of the TRUS biopsies in our study. Investigators have, however, found no learning curve associated with the procedure in studies that assessed the cancer detection rate [21,22].…”
Section: Number Of Biopsiesmentioning
confidence: 98%